Study of enzymolysis technology and microwave Maillard preparation of Litopenaeus vannamei. Issue 1 (1st January 2019) - Xiao, Chao-Geng; Wu, Jiang-Yan; Meng, Xiang-He; Tang, Hong-Gang; Chen, Li-Hong; Wu, Xu-Feng; Shen, Yue-Jun
ABSTRACT: The best enzymolysis conditions that fit actual production were determined via multiple-enzyme hydrolysis of waste shrimp heads through orthogonal experiment, taking frozen Litopenaeus vannamei as the starting material. The parameters including a material-water ratio of 1:4, initial pH of 8.5 and enzyme dosage of 0.4% contributed to average DH (degree of hydrolysis) value of 18.38% when the reaction was carried out at 55°C for 5 h. Microwave Maillard reaction of enzymatic hydrolysate was then performed to develop shrimp flavor juice, the optimal preparation conditions were determined based on reaction extent and sensory evaluation, including a power of 200W, temperature of 90°C and duration time of 30 min, with the addition of 3% reducing sugar and 3% amino acid.